Analysis of the Application of Profit Sharing on Marhamah's Savings Using Mudharabah Contracts at PT. Bank Sumut Sharia Karya Sub-Branch - Dara Khairatun Nisa Sinaga; Mustapa Khamal Rokan (Penerbit Jurnal Indonesia, 2022)
The purpose of this research is intended to identify and examine the application of profit sharing to savings marhamah using the mudharabah contract conducted by PT. Bank Sumut Karya Sub-Branch. In this study, the author uses a qualitative approach, namely a research method that emphasizes the aspect of in-depth understanding of a problem, so as to produce descriptive data. This study uses interview and documentation data collection techniques. The results of this study indicate that the application of profit-sharing savings marhamah by using the mudharabah contract by PT. Bank Sumut Syariah Capem Karya uses the profit sharing method, which is to share net profits from businesses or investments that have been carried out. So the application of the profit sharing system applied by PT. Bank Sumut Syariah Capem Karya has been running in accordance with fatwa No. 07/DSN-MUI/IV/2000.